Assesment of Smarandache Curves in The Null Cone Q2 - Kulahci, Mihriban Alyamac; Almaz, Fatma (Univ Punjab, Dept Mathematics, 2019)
In this study, Smarandache curves according to the asymptotic orthonormal frame are given in null cone Q(2). By using cone frame formulas, some characterizations of Smarandache curves are obtained and cone frenet invariants of these curves are calculated. Also, these curves are illustrated with an example.
Keywords: Smarandache curve; asymptotic orthonormal frame; null cone; cone frame formulas